1992
DOI: 10.1099/0022-1317-73-12-3195
|View full text |Cite
|
Sign up to set email alerts
|

Protein synthesis in pupae of the silkworm Bombyx mori after infection with nuclear polyhedrosis virus: resistance to viral infection acquired during pupal period

Abstract: Protein synthesis has been studied in pupae of the silkworm Bombyx mori (Bm) infected with nuclear polyhedrosis virus (BmNPV) at various stages of the pupal period. Nascent proteins were labelled by injection of [3sS]methionine into pupae and then analysed by SDS-PAGE. Temporal regulation of synthesis of infected cell-specific proteins (ICSPs) in pupae was demonstrated by electrophoretic analysis of the proteins labelled at different times post-infection (p.i.). The rate of ICSP synthesis reached a maximum at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(19 reference statements)
0
5
0
Order By: Relevance
“…Compared with silkworm larvae or insect cells, silkworm pupae are more convenient and economical to be a carrier to efficiently produce large quantities of heterologous proteins Mikhailov et al 1992;Motohashi et al 2005;Wang et al 2005). Experiments demonstrated that the pupae, being non-toxic and highly nutritious Per Se, can be regarded as a top class unconventional protein and energy feed and utilized directly for poultry and fisheries (Khatun et al 2005;Rangacharyulu et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…Compared with silkworm larvae or insect cells, silkworm pupae are more convenient and economical to be a carrier to efficiently produce large quantities of heterologous proteins Mikhailov et al 1992;Motohashi et al 2005;Wang et al 2005). Experiments demonstrated that the pupae, being non-toxic and highly nutritious Per Se, can be regarded as a top class unconventional protein and energy feed and utilized directly for poultry and fisheries (Khatun et al 2005;Rangacharyulu et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…There are several benefits to baculoviruses that encode an EGT. Ecdysteroids induce physiological modifications that decrease insect permissivity to baculovirus infection (O'Reilly et al, 1995(O'Reilly et al, , 1998; by altering these hormones, baculoviruses prevent the developmental resistance to virus replication observed in caterpillars (Keeley & Vinson, 1975;Murray et al, 1991;Mikhailov et al, 1992;Engelhard & Volkman, 1995;Washburn et al, 2001). Moults and pupation monopolize important insect biological resources and are associated with an arrest of food ingestion Flipsen et al, 1995;Shikata et al, 1998;Slavicek et al, 1999;Bianchi et al, 2000;Chen et al, 2000;Dai et al, 2000;Wilson et al, 2000;Sun et al, 2002).…”
Section: Ecdysteroid Glucosyltransferase Encoded By Baculovirusesmentioning
confidence: 99%
“…Cell nuclei were isolated from mouse brains according to the procedure described by Mikhailov et al . (1992).…”
Section: Isolation and Fractionation Of Cell Nucleimentioning
confidence: 99%
“…Cell nuclei were isolated from mouse brains according to the procedure described by Mikhailov et al (1992). Briefly, mouse brains were homogenized on ice in Buffer A (50 mM Tris-HCl, pH 7.5; 10 mM KCl; 10 mM MgCl 2 ; 1 mM CaCl 2 ; 2 mM dithiothreitol; 0.3 M sucrose) (1 brain/4 mL) with a Dounce homogenizer (20 strokes with loose-fitting pestle and 10 strokes with tight-fitting pestle).…”
Section: Isolation and Fractionation Of Cell Nucleimentioning
confidence: 99%